Identification of microRNA targets for the alternative splicing isoforms of CD46. - Teo, Zhi Lin. (2013)
CD46 is a transmembrane protein that is expressed on all nucleated host cells. Other than being involved in the complement pathway, defects in CD46 or CD46-mediated signals are also linked to human autoimmune diseases. Some tumor cells are found to overexpress CD46, suggesting its probable role in cancer. Given the multitude roles of CD46, its regulation should have important implications in many biological processes. One class of regulatory molecules that can regulate gene expression is the miRNAs. Currently, only miRNA-520 (miR-520) has been found to target the 3’UTR of CD46. Finding miRNA targets in the 3’UTR should have important implications in further elucidation of the function of CD46 and providing possible therapeutics in CD46-linked diseases. Therefore, in this study, the aim is to identify more miRNA targets for CD46. Deletions were made to the 3’UTR of CD46 and the expression of these minigenes with deletions were analysed using the Dual-Glo Luciferase Assay. Statistical analysis of the luciferase ratios showed that several regions within the 3’UTR of CD46 may contain miRNA target sites. The analysis also showed that miR-186 and miR-140-5p may target the CD46 3’UTR. These findings are preliminary and further experiments are needed to validate the results.